Retinal mesopic adaptation model for brightness perception under transient glare - Barrionuevo, Pablo Alejandro (2013)
A glare source in the visual field modifies the brightness of a test patch surrounded by a mesopic background. In this study, we investigated the effect of two levels of transient glare on brightness perception for several combinations of mesopic reference test luminances (Lts) and background luminances (Lbs). While brightness perception was affected by Lb, there were no appreciable effects for changes in the Lt. The highest brightness reduction was found for Lbs in the low mesopic range. Considering the main proposal that brightness can be inferred from contrast and the Lb sets the mesopic luminance adaptation, we hypothesized that contrast gain and retinal adaptation mechanisms would act when a transient glare source was present in the visual field. A physiology-based model that adequately fitted the present and previous results was developed.